Impact of sensory adapted dental environment on children with developmental disabilities. (6th February 2019) - Kim, Gail; Carrico, Caroline; Ivey, Carole; Wunsch, Patrice B.
Abstract: Aims: This was a pilot study assessing the impact of a sensory adapted dental environment (SADE) on children with developmental disabilities (DD) receiving routine dental care. Methods: A crossover study of 22 children with DD, aged 6 through 21, was conducted at a University Pediatric Dental clinic. Each participant was randomized to a sequence of two dental cleanings on a 3‐ to 4‐month recall schedule, one with a regular dental environment (RDE) and one with SADE. Outcomes included physiological measures (heart rate and oxygen saturation) and cooperation (Frankl scores). Results: Study subjects completed 36 visits. None of the physiological measures differed at either time point between the two treatment settings. The Frankl scores were significantly higher with SADE setting than RDE ( P =  0.0368). Forty‐six percent of parents strongly agreed that they would prefer the SADE for their child's next visit. Conclusion: SADE may be associated with improved behavior in children with DD.